Education, Knowledge and Nutritional Status of Elderly in Elderly Integrated Service Post Working Area of Bentiring Community Health Center Bengkulu - Nurul Khairani; Santoso Ujang Effendi; Desi Kurnia Putri (Jurnal Sains Kesehatan, 2018)
This study was based on the still high nutrient deficiency of  elderly in                  the working area of  Bentiring  Community  Health  Center   Bengkulu. This study aimed to study the relationship between education and knowledge with                        nutritional  status of  elderly in  Elderly  Integrated  Service  Post  working  area  of   Bentiring  Community  Health  Center Bengkulu. The  research type was Analytical Survey and the desain of research was Cross Sectional. The population of  this  study  was  all  elderly who visited  Elderly Integrated  Service Post                in  the  working  area  of Bentiring Community  Health  Center  Bengkulu                   in January to April 2017 which amounted to 52 elderly. Sampling technique in this research used   Total  Sampling. The data collected in this study used primary data and secondary data with data analysis technique done by univariate and bivariate analysis with Chi-Square test (c²) through SPSS 16 program. The result of  this research were : from 52 elderly,  there were  35 elderly (67,3%)  with basic education, 27 elderly  (51,9%)  who had  less knowledge, 20 elderly  (38,5%)  had  less  nutritional  status, there was significant relationship  between  education  with  nutritional  status of  elderly  with  medium category, and there was a significant relationship between knowledge with nutritional status  of  elderly with close category. It was expected to Bentiring Community Health Center Bengkulu to improve health services to the elderly by providing nutrition education and medical  examination  for  elderly.  Keywords : education, elderly, knowledge, nutritional status, elderly